Degradation of plastic waste using stimulated and naturally occurring microbial strains. (January 2021) - Taghavi, Navid; Singhal, Naresh; Zhuang, Wei-Qin; Baroutian, Saeid
Abstract: The capability of different strains derived from soil, activated sludge, farm sludge, and worms' excreta were investigated for biodegradation of high-density polyethylene, polystyrene foam, polypropylene and polyethylene terephthalate in unstimulated and stimulated conditions. Biodegradation using naturally occurring microbial strains examined in mixed (270 days) and individual (100 days) systems, while H2 O2 stimulated strains were tested only in the mixed system (30 days). Penicillium raperi, Aspergillus flavus, Penicillium glaucoroseum and Pseudomonas sp. were isolated as the most plastic degrading microbes. Maximum weight loss was seen by incubation of polyethylene with Aspergillus flavus (5.5%) in unstimulated mix condition. Fourier Transform Infrared Spectroscopy (FT-IR) revealed formation of new functional groups as hydroxyl, carbonyl, alkene and alkoxy in the treated plastics. Visualisation of plastics by optical, atomic force (AFM) and electron microscopy (SEM) were also illustrated biodegradation. The derived by-products from microbial degradation was tested, and found no inhibition on microbial growth and performance. Highlights: Penicillium, Aspergillus and Pseudomonas sp. isolated as plastic degrading strains. The isolated strains showed biofilm formation and ability to degrade PET, PS and PE. A higher surface degradation was observed using the mixed microbial systems. Maximum 5.5% weight loss of HD-PE obtained within 100 days. Stimulation can reduce degradation time with having 2.5% weight loss in 30 days.